Responses in acral and non-acral skin vasomotion and temperature during lowering of ambient temperature - Elstad, Maja; Vanggaard, Leif; Lossius, Astrid H; Walløe, Lars; Kristin Bergersen, Tone (Journal of thermal biology, 2014)
Arteriovenous anastomoses (AVA) in acral skin (palms and soles) have a huge capacity to shunt blood directly from the arteries to the superficial venous plexus of the extremities. We hypothesized that acral skin, which supplies blood to the superficial venous plexus, has a stronger influence on blood flow adjustments during cooling in thermoneutral subjects than does non-acral skin. Thirteen healthy subjects were exposed to stepwise cooling from 32°C to 25°C and 17°C in a climate chamber. Laser Doppler flux and skin temperature were measured simultaneously from the left and right third finger pulp and bilateral upper arm skin. Coherence and correlation analyses were performed of short-term fluctuations at each temperature interval. The flux from finger pulps showed the synchronous spontaneous fluctuations characteristic of skin areas containing AVAs. Fluctuation frequency, amplitude and synchronicity were all higher at 25°C than at 32°C and 17°C (p<0.02). Bilateral flux from the upper arm skin showed an irregular, asynchronous vasomotor pattern with small amplitudes which were independent of ambient temperature. At 32°C, ipsilateral median flux values from the right arm (95% confidence intervals) were 492 arbitrary units (au) (417, 537) in finger pulp and 43au (35, 60) in upper arm skin. Flux values gradually decreased in finger pulp to 246au (109, 363) at 25°C, before an abrupt fall occurred at a median room temperature of 24°C, resulting in a flux value of 79au (31, 116) at 17°C. In the upper arm skin a gradual fall throughout the cooling period to 21au (13, 27) at 17°C was observed. The fact that the response of blood flow to ambient cooling is stronger in acral skin than in non-acral skin suggests that AVAs have a greater capacity to adjust blood flow in thermoneutral zone than arterioles in non-acral skin. •Arteriovenous anastomoses in acral skin are more potent in adjusting blood flow within thermoneutral zone than arterioles in non-acral skin.•Fluctuation frequency and amplitude of blood flow through the arteriovenous anastomoses are highest in ambient temperature above 24°C.•Studies on acral blood flow should be performed in ambient temperatures above 24°C.